Exploring the benefits of nature-based interventions in socio-economically deprived communities: a narrative review of the evidence to date. (May 2023) - Harrison, H; Burns, M; Darko, N; Jones, C
Aim: Socio-economic deprivation encompasses the relative disadvantage experienced by individuals or communities in relation to financial, material or social resources. Nature-based interventions (NBIs) are a public health approach that promote sustainable, healthy communities through engagement with nature and show potential to address inequalities experienced by socio-economically deprived communities. This narrative review aims to identify and evaluate the benefits of NBIs in socio-economically deprived communities. Method: A systematic literature search of six electronic publication databases (APA PsycInfo, CENTRAL, CDSR, CINAHL, Medline and Web of Science) was conducted on 5 February 2021 and repeated on 30 August 2022. In total, 3852 records were identified and 18 experimental studies (published between 2015 and 2022) were included in this review. Results: Interventions including therapeutic horticulture, care farming, green exercise and wilderness arts and craft were evaluated in the literature. Key benefits were observed for cost savings, diet diversity, food security, anthropometric outcomes, mental health outcomes, nature visits, physical activity and physical health. Age, gender, ethnicity, level of engagement and perception of environment safety influenced the effectiveness of the interventions. Conclusion: Results demonstrate there are clear benefits of NBIs on economic, environmental, health and social outcomes. Further research including qualitative analyses, more stringent experimental designs and use of standardised outcome measures is recommended.